1989
DOI: 10.1037/0097-7403.15.1.75
|View full text |Cite
|
Sign up to set email alerts
|

Multiple-food-unit-incentive effect: Nonconservation of weight of food reward by rats.

Abstract: A common assumption is that the incentive value of food is determined by weight independently of number of food units. In Experiments 1 and 2, rats trained in a T-maze with four 75-mg pellets in one alternative and a single 300-mg pellet in the other alternative developed a preference for the 75-pellet alternative, which did not diminish with extensive training. When the locations of the 75-mg and 300-mg pellets were reversed, rats reversed their choice of arm. Rats preferred a 300-mg pellet to four 45-mg pell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
24
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 10 publications
5
24
2
Order By: Relevance
“…For instance, in a study of operant conditioning in chickens, a kernel of corn divided into four pieces was found to be a more effective reinforcer than the whole kernel. Similar results have been demonstrated in studies of rats; for instance, it has been found that rats preferred four small food pellets as opposed to one large food pellet (Capaldi et al 1989). In studies of people, self-esteem was enhanced when a single statement, containing positive attributes (e.g., I am creative, analytical, and verbal) about oneself was divided into distinct statements (e.g., I am creative; I am analytical; I am verbal) (Showers 1992).…”
Section: Numerosity Heuristic and Difference Assessmentssupporting
confidence: 63%
“…For instance, in a study of operant conditioning in chickens, a kernel of corn divided into four pieces was found to be a more effective reinforcer than the whole kernel. Similar results have been demonstrated in studies of rats; for instance, it has been found that rats preferred four small food pellets as opposed to one large food pellet (Capaldi et al 1989). In studies of people, self-esteem was enhanced when a single statement, containing positive attributes (e.g., I am creative, analytical, and verbal) about oneself was divided into distinct statements (e.g., I am creative; I am analytical; I am verbal) (Showers 1992).…”
Section: Numerosity Heuristic and Difference Assessmentssupporting
confidence: 63%
“…Investigators use the two bottle test [10,16], which includes a working chamber fi tted with food reservoirs located outside the chamber, and tubes in the working sector allowing the animals to access test liquid foods with different taste properties or different concentrations of test food substances (saccharine, fructose, etc.). This apparatus provides for study of food preference based on taste reception of different samples of edible food and/or its calorifi c value, but it does not provide for studies of the role of the primary (sensory) reinforcement associated with the remote actions of natural food stimuli (food type, quantity, size, color) which are used by subjects to assess the attractant properties of the test foods and make the choice before taking and eating.Another method for studying food preference in rodents by presenting the animals with various food samples in solid form is also known [8,15]. In these experiments, selection of the preferred food (food granules and tablets of different sizes and weights) is performed manually by the animals by combined use of the tactile, muscular, and taste analyzers.…”
mentioning
confidence: 99%
“…Another method for studying food preference in rodents by presenting the animals with various food samples in solid form is also known [8,15]. In these experiments, selection of the preferred food (food granules and tablets of different sizes and weights) is performed manually by the animals by combined use of the tactile, muscular, and taste analyzers.…”
mentioning
confidence: 99%
See 2 more Smart Citations